ELECTROLYTIC OXIDATIONOF TETRA- HYDROCARBAZOLE (Biological Sciences - PJSIR, 2004)
THC was oxidized by a similar mechanism in the presence and absence of bicarbonate. A Bioanalytical Systems BAS-100 Electrochemistry System was used for voltammetry.